Perkembangan Terkini Membran Guided Tissue Regeneration/Guided Bone Regeneration sebagai Terapi Regenerasi Jaringan Periodontal - Cindy Cahaya; Sri Lelyati C Masulili (Majalah Kedokteran Gigi Indonesia, 2015)
Latest Development of Guided Tissue Regeneration and Guided Bone Regeneration Membrane as Regenerative Therapy on Periodontal Tissue. Periodontitis is a patological state which influences the integrity of periodontal system that could lead to the destruction of the periodontal tissue and end up with tooth loss. Currently, there are so many researches and efforts to regenerate periodontal tissue, not only to stop the process of the disease but also to reconstruct the periodontal tissue. Periodontal regenerative therapy aims at directing the growth of new bone, cementum and periodontal ligament on the affected teeth. Regenerative procedures consist of soft tissue graft, bone graft, roots biomodification, guided tissue regeneration and combination of the procedures, including restorative surgical procedure that is connected with oral rehabilitation with implant placement. At cellular phase, periodontal regeneration is a complex process with well-organized proliferation, distinction, and development of various type of cell to form attachment of periodontal tissue. Rationalization of the use of guided tissue regeneration as barrier membrane is to prohibit the penetration of epithelial and connective tissue migration into the defect, to maintain space, and to stabilize the clot. This research discusses: 1. Healing process on periodontal therapy including regeneration, repair or formation of new attachment. 2. Periodontal specific tissue engineering. 3. Various commercially available membrane/guided tissue regeneration in the market with its advantages and disadvantages and their characteristics. 4. Recent advancement of membrane as regenerative therapy on periodontal disease. In addition, this review is presented to give an outlook for promising regenerative therapy as a part of developing knowledge and skills to treat periodontal disease.